TATA KELOLA HUBUNGAN MASYARAKAT DI LEMBAGA PENDIDIKAN KUTTAB: id - Ari Prayoga; Irfan Setia Permana; Della Shelvira (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2021)
Kuttab is considered foreign to some people so that the public is still familiar with the concept of kuttab education. Historically, the Muslim community did not allow the Kuttab to be separate and there were boundaries with society. It is for this that the Kuttab correlates with its people and joins in their daily lives. The existence of a barrier between kuttab and society can affect people's beliefs and participation. The purpose of this research is to identify and describe the Governance of Public Relations in Kuttab Al Fatih Bandung from planning, implementation, assessment, to supporting and inhibiting aspects of public relations at Kuttab Al Fatih Bandung. The method used in this research is qualitative. Data collection used observation procedures, interviews and documentation research. The data validity test used the participation extension technique, observer intensity, triangulation, peer checking, referral adequacy, negative problem analysis, member checking, detailed explanation and auditing. The results of this research show that the governance of public relations in Kuttab Al Fatih Bandung is running well even though this task is held by the official Kuttab and the Tawaf division. First, planning refers to the vision, mission and profile of Kuttab Al Fatih Bandung which refers to the Al-Quran, hadith and the prophet's sirah. Second, implementation is carried out by implementing planned programs that involve all kuttab stakeholders. Third, evaluation is carried out after programs and activities have been implemented. This evaluation is to take into account the success of the program and deliberate on any cases. Fourth, the supporting aspects of public relations come from internal Kuttab, namely Kuttab's human resources who have a sincere mindset and the intention to worship when carrying out all activities. The factors inhibiting citizen ties come from externals, namely parents and residents who have different descriptions of the concept of Kuttab education.